Prior mathematics achievement and mathematics self-efficacy as indicators for success in pre-service teachers’ achievement in geometry and trigonometry - Agormor, Sefakor; Apawu, Jones; Aboagye-Agbi, Jackson Jessel; Hokor, Evans Kofi (Journal of Research in Instructional, 2022)
This study is a quantitative research and used a correlational research design to investigate the relationship between pre-service teachers’ prior mathematics achievement (PA) at the senior high school and mathematics self-efficacy (MSEF) on learning and achievement in geometry and trigonometry in colleges of education. A sample of 449 pre-service teachers (264 males and 185 females) randomly selected from the population was used for the study. The result revealed a strong positive relationship between PA (r = 0.543), MSEf (r = 0.542), and geometry and trigonometry score. The study then concludes that the factors (PA, MSEf) have a positive relationship with geometry and trigonometry achievement. The study recommended that colleges of education should place much emphasis on pre-service teachers’ entry grade in mathematics when considering the requirement for admission.